Influence Supervisory and Organizational Commitment on Employee Work Discipline With Employee PerformanceAs An Intervening Variable In Tomo Sub-District The Sumedang Distric - ipa Hafsiah Yakin (SINTESA, 2023)
The focus of this research is not optimal employee discipline in Tomo District. The purpose of this research is to find out how big the influence of supervision, organizational commitment to employee work discipline with implications for performance employee of Tomo District, Sumedang Regency. The method used in the research This is a survey method with a quantitative approach. The number of respondents in the study There were 67 respondents consisting of village officials and apparatus in Tomo District. The results of the study show that supervision has a partial effect on work discipline employees by 0.343 or 34.3%. Organizational commitment has a partial effect on employee work discipline of0.827 or 82.7%. Supervison and organizational commitment together have a simultaneous effect on performance of 0.922 or 92.2%. Supervision has a partial effect on employee performance by 0.636 or 63.6%. Organizational commitment has a partial effect on employee performance of 0.383 or 38.3%. Supervison andOrganizational Commitment together are simultaneously influential on employeeperformance by 0.850 or 85%. Work discipline has a partial effect on employee performance by 0.748 or 74.8%. Supervision and employee work discipline simultaneously affect employee performance by 0.636 or 63.6%. Commitment organization and employee work discipline affect employee performance by 0.383or 38.3%.